Self-Driving Cars and Rural Areas: The Potential for a Symbiotic Relationship - Chmielewski, Christiana (Journal of Law and Commerce, 2019)
Imagine getting in the driver’s seat of your car, setting your destination, then sitting back and watching a movie, answering emails, or even taking a nap during the ride. While this is hardly a new concept for passengers, it is a new phenomenon for the person in the driver’s seat. Now, imagine driving down a winding country road in the middle of the night when a white-tailed deer darts out in front of you. Your instinct is to slam on the brakes and jerk the wheel, an instinct that can often have devastating results for you, your car, and the deer. In a self-driving car, human panic, and therefore human error, is eliminated. Part I of this note begins with a general background on self-driving vehicles and their development to date. Part II provides a description of rural areas, including the classification of rural areas and their demographics. Part III examines current state laws that address self-driving vehicles, focusing on Pennsylvania. Part IV discusses why self-driving vehicles should be introduced to rural areas for testing. Part V reviews car accident statistics in Allegheny County and its rural neighbor Butler County, then compares and discusses these statistics to demonstrate how self-driving cars could have an immediate beneficial effect on rural areas. Part VI addresses the basic logistics of choosing the rural area to test drive and proposes how to select test drivers. Finally, Part VII addresses potential counterarguments to the introduction of self-driving vehicles in rural areas.